RFID based Authorization Method for Computer Systems in Smart Library Environments - Bayğın, Mehmet; Yaman, Orhan; Topuz, Arif Cem; Kaleli, Salih Serkan (My University, 2021)
In recent years, intelligent systems have emerged with the concept of the Internet of Things. The purpose of intelligent systems is to use technological innovations to improve the quality of life of people. Smart systems are now being used almost everywhere. Concepts such as smart city, smart classroom, smart library, smart hospital and smart transportation have emerged. With the cameras, sensors and many other devices used in smart systems, data from the environment can be analyzed and remote control operations can be performed. In this study, RFID based authorization system has been developed in the publicly available computers used in smart libraries. In many places, as in universities, there are common computers or laboratory devices that can be used by everyone. The aim of this study is to ensure the common use of devices belonging to common use against existing users. The devices are controlled by an RFID based system developed for these devices. Using the ID cards of the students or staff, the person is authorized to use the devices for the defined period of time. This study has two main contributions. First, a modular system compatible with all electronic devices except the computer has been made by using RFID technology. The second is to provide a more efficient working environment by ensuring fair use of computers and other devices accessible.
Keywords: Bilgisayar Bilimleri; Yazılım Mühendisliği; Bilgisayar Bilimleri; Bilgi Sistemleri